Study of International Experience in the Implementation of Fiscal Policy in the Context of Financial Decentralization - Martynenko, Valentyna Vitaliivna (Cech Rzemiosł Różnych, 2018)
This article discusses the features of the implementation of the fiscal policy of the state in the context of financial decentralization, taking into account the experience of both the federal system and unitary states in order to adapt their experience to the realities of Ukraine. The author proves that at the present stage in the implementation of fiscal policy the key place is occupied by financial decentralization. Necessary and sufficient principles of decentralization are formulated and advantages of fiscal federalism are characterized. The importance of financial decentralization creates possible manifestations of its potential, but does not provide an automatic solution to the economic and financial problems of budgetary resources management. In this regard, the author argues that the necessary condition for financial decentralization in the fiscal policy of the state is, at least, to prevent the reduction of the achieved level of public finance management, and to choose the optimal balanced model of its implementation. To do this, it is necessary to determine the range of tasks that can be most effectively solved by the central authorities and adequately financed from the state budget; to determine the tasks that require decentralized solutions. The typical models of distribution of powers between central and municipal authorities, which exist in the world, are analyzed in order to use them as indicators in the implementation of the reform of financial decentralization in Ukraine. In particular, the author substantiates the need for a clear distribution of fiscal powers; informed decision-making; compliance with local priorities; introduction of local government accountability.

У цій статті розглядаються особливості реалізації фіскальної політики держави в умовах фінансової децентралізації з урахуванням політики держави в умовах фінансової децентралізації, з урахуванням досвіду як країн федеративного ладу, так і унітарних досвіду як країн федеративного устрою, так і унітарних держав з метою адаптації їхнього досвіду в реалії України. Автором обґрунтовано, що на сучасному етапі під час реалізації фіскальної політики ключове місце посідає фінансова децентралізація. Сформульовано необхідні та достатні принципи децентралізації та охарактеризовано переваги фіскального федералізму. Суперечливість значення фінансової децентралізації формує можливі прояви її потенціалу, але не забезпечують автоматичного вирішення економічних і фінансових проблем управління бюджетними ресурсами. У цьому зв'язку автор доводить, що необхідною умовою проведення фінансової децентралізації у фіскальній політиці держави є, як мінімум, недопущення зниження досягнутого рівня управління публічними фінансами, та вибору оптимальної виваженої моделі її проведення. Для цього необхідно визначити коло завдань, які найбільш ефективно можуть бути вирішені центральними органами влади і відповідним чином фінансуватися з державного бюджету; визначити завдання, які потребують децентралізованих рішень. Проаналізовано типові моделі розподілу повноважень між центральним і муніципальними органами державної влади, які існують у світі, з метою використати їх як індикатори під час реалізації реформ. їх як індикатори під час реалізації реформи фінансової децентралізації в Україні. Зокрема, автор обґрунтовує необхідність чіткого розподілу фіскальних повноважень; прийняття обґрунтованих рішень; дотримання місцевих пріоритетів; запровадження підзвітності місцевих урядів.
Keywords: fiscal policy; financial decentralization; federalism; principle; local authorities; powers; фіскальна політика; фінансова децентралізація; федералізм; принцип; місцеві органи влади; повноваження